SAFETY OF LAMOTRIGINE IN PAEDIATRICS: A SYSTEMIC REVIEW. Issue 1 (14th December 2015) - Egunsola, Oluwaseun; Choonara, Imti; Sammons, Helen
Abstract : Background: Lamotrigine has been increasingly used for the treatment of paediatric epilepsy. It is the most commonly prescribed new generation antiepileptic drug in the UK. Objectives: To identify adverse drug reactions associated with lamotrigine in children, compare the safety profile with other antiepileptic drugs and identify all clinical studies and case reports involving lamotrigine safety in children. Methods: Databases EMBASE (1974-November 2013), Medline (1946-November 2013), PubMed and the Cochrane library for randomised controlled trials were searched for original research or reports in which paediatric patients received at least a single dose of lamotrigine for the treatment of epilepsy, with safety as an outcome measure. Results: A total of 76 articles involving 2, 184 paediatric patients were identified. There were 1, 952 adverse events (AEs) reported. Fifty two of these AEs were from 49 case reports. Rash was most commonly reported, with a risk of 8.96 per 100 patients. Other common AEs included headache, fever, somnolence, vomiting, seizure aggravation, dizziness, cough, aggression, ataxia and insomnia. There were significantly higher risks of dizziness [RR 4.57, 95% CI: 1.88–11.12, p<0.001], abdominal pain [RR: 2.53, 95% CI: 1.12–5.70, p=0.03] and nausea [RR: 5.94, 95% CI: 1.59–22.13, p=0.008] with lamotrigine than placebo. When compared with valproic acid, the risk of somnolence and vomiting was significantly lower for lamotrigine [RR: 0.35, 95% CI: 0.13–0.89, p=0.04] and [RR: 0.20, 95% CI: 0.04–0.89, p=0.03]. Discontinuation due to an adverse drug reaction was recorded in 72 children (3.2% of all treated patients). Rash was the most common reason, with 58% of treatment discontinuation attributed to different forms of rash. Conclusion: Rash is the most common adverse reaction of lamotrigine, seen in around 9% of patients, and it is the most common reason for treatment discontinuation.